Low cost adsorbent for mitigation of water pollution caused by tannery effluents at Hazaribagh (Bangladesh Journal of Scientific and Industrial Research, 2016)
Tanneries at Hazaribagh use a large number of chemicals during processing and discharge their effluents to the river Buriganga without appropriate treatment and aggravate its pollution level. This study focuses on a plausible way for the abatement of pollution level of Buriganga river water using low cost adsorbent. Activated carbon prepared from coconut shell was used as a low cost adsorbent. The samples were collected from three different points of the river at three different layers from the surface of water. The collected samples were passed through the activated carbon and a remarkable amount of pollutants were found to be adsorbed. TSS, TDS, BOD5, COD and chromic oxide content of polluted water were reduced significantly.Bangladesh J. Sci. Ind. Res. 51(3), 215-220, 2016